2020
DOI: 10.1101/2020.12.20.423630
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutation Landscape of SARS COV2 in Africa

Abstract: COVID-19 disease has had a relatively less severe impact in Africa. To understand the role of SARS CoV2 mutations on COVID-19 disease in Africa, we analysed 282 complete nucleotide sequences from African isolates deposited in the NCBI Virus Database. Sequences were aligned against the prototype Wuhan sequence (GenBank accession: NC_045512.2) in BWA v. 0.7.17. SAM and BAM files were created, sorted and indexed in SAMtools v. 1.10 and marked for duplicates using Picard v. 2.23.4. Variants were called with mpileu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
(58 reference statements)
1
3
0
Order By: Relevance
“…Finally, the two mutations that were first identified in the present study (ORF3a_T269del, M_L54F) concern residues with previously detected variation (CoV-GLUE Mutations), which could partly explain our findings. These data, including the presence of less common mutations that were identified in the randomly selected SARS-CoV-2 genome sequences of our study and of previous studies with small cohorts of patients [ 39 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ], further confirm the existence of variation in the genomic sequence, regardless of whether these mutations have been established worldwide producing new viral lineages or not. Viral genome evolution during the first wave of the pandemic has been characterized by the emergence of sets of substitutions that led to the establishment of more than one new viral strain [ 115 , 116 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Finally, the two mutations that were first identified in the present study (ORF3a_T269del, M_L54F) concern residues with previously detected variation (CoV-GLUE Mutations), which could partly explain our findings. These data, including the presence of less common mutations that were identified in the randomly selected SARS-CoV-2 genome sequences of our study and of previous studies with small cohorts of patients [ 39 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ], further confirm the existence of variation in the genomic sequence, regardless of whether these mutations have been established worldwide producing new viral lineages or not. Viral genome evolution during the first wave of the pandemic has been characterized by the emergence of sets of substitutions that led to the establishment of more than one new viral strain [ 115 , 116 ].…”
Section: Discussionsupporting
confidence: 86%
“…ORF1ab_H417R, which has been detected in a meta-analysis study, has also been shown to be carried by Brazilian patients [36,107]. ORF1ab_L3606F, which has been described as a homoplastic mutation [75], was observed in China for the first time [59] and has also been reported in studies concerning Italy [59], Brazil [59], Iran [108], Africa [109] and in other studies that do not specify geographic regions [62,[67][68][69]120]. Moreover, ORF1ab_Y4847Y, which was not present in China at the early stages of the worldwide viral spread [110], was detected in large-scale studies [59,65,76,77] and placed in Malaysia in the third wave of the pandemic [110], in Thailand in the first wave [111], in Korea [112], in Oceania [77], in Europe [76,77], in Spain, in North America and in Australia [76].…”
Section: Discussionmentioning
confidence: 98%
“…21,22 Variants of SARS-CoV-2 are further being assessed, to determine whether a specific variant's transmissibility, clinical presentation, severity, or impact on countermeasures (i.e., diagnostics, therapeutics, and vaccines) hinders the disease process. 9,14,15,23 Therefore, priority has been placed on tracking the following mutations circulating worldwide: D614G (B.1 lineage), N501Y (several lineages), E484K (several lineages), K417 (several lineages), L452R (several lineages), Q677 (several lineages), and others. 9 D614G, a mutation of SARS-CoV-2 which emerged in early 2020, has a substitution in the gene encoding the S protein.…”
Section: Variants Of Sars-cov-2mentioning
confidence: 99%
“…PLpro is encoded in the NSP3 region of ORF1a, which was demonstrated to be a site with the largest number of missense variants out of 16 ORF1ab proteins [14,31]. Moreover, some substitutions were proved to reduce activity of SARS-CoV and SARS-CoV-2 PLpro with Ub and ISG15 [29,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%